2017
DOI: 10.1249/mss.0000000000001374
|View full text |Cite|
|
Sign up to set email alerts
|

Greater Effect of East versus West Travel on Jet Lag, Sleep, and Team Sport Performance

Abstract: Long-haul transmeridian travel can impede team sport physical performance. Specifically, east travel has a greater detrimental effect on sleep, subjective jet lag, fatigue, and motivation. Consequently, maximal and intermittent sprint performance is also reduced after east travel, particularly within 72 h after arrival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 37 publications
(12 reference statements)
1
53
0
Order By: Relevance
“…However, this finding may be confounded by the fact that pretravel sleep was monitored during a training camp, and that there was an increase in sleep opportunities on arrival 44. Nonetheless, there is evidence in subelite athletes that eastward travel is more disruptive to sleep than westward travel 105. These findings suggest consideration for the timing of flight departures and the direction of travel is necessary to mitigate the negative effects of air travel.…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding may be confounded by the fact that pretravel sleep was monitored during a training camp, and that there was an increase in sleep opportunities on arrival 44. Nonetheless, there is evidence in subelite athletes that eastward travel is more disruptive to sleep than westward travel 105. These findings suggest consideration for the timing of flight departures and the direction of travel is necessary to mitigate the negative effects of air travel.…”
Section: Discussionmentioning
confidence: 99%
“…The more east-west time zones crossed, the more difficult it may be to adapt. One study showed specifically traveling west to east on a long-haul flight had worse effects on sleep and subjective fatigue, motivation, and feelings of jet lag [57]. Sprint performance was also affected, especially in the first 72 h after landing [57].…”
Section: Mitigating Jet Lagmentioning
confidence: 99%
“…One study showed specifically traveling west to east on a long-haul flight had worse effects on sleep and subjective fatigue, motivation, and feelings of jet lag [57]. Sprint performance was also affected, especially in the first 72 h after landing [57]. Another study showed that not only long duration (up to 30h) but short (up to 6.5 h) duration east-west flights compromised sleep, increased fatigue and decreased vigor [58].…”
Section: Mitigating Jet Lagmentioning
confidence: 99%
“…The NBA travel schedule induces misalignments in circadian rhythm that cannot be avoided. Air travel across three time zones has been reported to induce susceptibility to travel fatigue [ 18 , 29 , 42 , 43 , 44 ], increase injury risk [ 13 , 29 , 41 ], and reduce game performance [ 13 , 14 , 17 , 29 , 32 ]. NBA schedule-makers and teams may succeed in mitigating the negative effects of air travel from coast to coast on sleep by implementing up-to-date, evidence-based strategies applied in other professional sports, such as blue light exposure in the morning and red light exposure in the evening, in order to resynchronize the circadian rhythms of players [ 45 ].…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…First, it is important to understand the impact of air travel on NBA players at an individual level, given that NBA players often experience time zone transitions, which have been found to increase injury risk [ 9 , 41 ] and hinder performance [ 15 , 19 , 21 , 40 , 42 , 47 ]. Considering frequent time zone transitions often disrupt the circadian rhythm in athletes [ 15 , 16 , 19 , 26 , 42 , 43 ], future studies may focus on the measurement of salivary melatonin onset, adrenaline concentrations, and body temperature, as these are critical biomarkers of circadian rhythm [ 19 , 48 ]. Measurement of these biomarkers would provide insight into how each player individually adapts to air travel throughout the NBA season.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%